Answer :

We have,

…(i)


…(ii)


Now, substituting and in (i) and (ii) we get:


3u + 2v = 2 …(iii)


9u – 4v = 1 …(iv)


Multiplying (iii) by 2 and adding it with (iv) we get:


6u + 9u = 4 + 1




Multiplying again (iii) by 2 and then subtracting it from (iv), we get:


6v + 4v = 6 – 1




x + y = 3 …(v)


And, x – y = 2 …(vi)


Now, by adding (v) and (vi) we get:


2x = 3 + 2



Substituting the value of x in (v), we get






Hence, option B is correct

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

<span lang="EN-USMathematics - Board Papers

A father&rsMathematics - Board Papers

Find the value ofRS Aggarwal - Mathematics

Find the value ofRS Aggarwal - Mathematics

A man purchased 4RS Aggarwal - Mathematics